Party-political and electoral system of Uruguay - Decresci, Samuel (Laboratório Editorial Faculdade de Ciências e Letras, 2015)
The Oriental Republic of Uruguay is seen by many as a pioneer among Latin American nations to modernize its state and its policy. Since the late nineteenth century to the twentieth, Uruguayan political actors operate significant changes such as the separation of church and state, labor regulation, divorce law, women's vote, etc. Because of this and the progressive modernization, it was called the “Switzerland of the Americas”. Today, it still stands out in this area by regularizing abortion, homoaffective marriage, liberalization and access to marijuana. Moreover, noteworthy that such measures were achieved largely because of governance that the executive enjoys in the midst of this political system. Thus, this work aims to analyze such Uruguayan political system. In short, a political system is understood by the government system, the electoral system and the party system. That said, it will be analyzed in the political scenario of the country, their characteristics, party and election rules, political parties, party dynamics and relations between the powers.